Advances in Atmospheric Radiation: Theories, Models, and Their Applications. Part II: Radiative Transfer Models and Related Applications - Zhang, Hua; Zhang, Feng; Liu, Lei; Liu, Yuzhi; Letu, Husi; Yang, Yuanjian; Li, Zhengqiang; Wu, Kun; Hu, Shuai; Li, Ming; Dai, Tie; Wang, Fei; et al. (Journal of Meteorological Research, 2024)
The subject of “atmospheric radiation” includes not only fundamental theories on atmospheric gaseous absorption and the scattering and radiative transfer of particles (molecules, cloud, and aerosols), but also their applications in weather, climate, and atmospheric remote sensing, and is an essential part of the atmospheric sciences. This review includes two parts (Part I and Part II); following the first part on gaseous absorption and particle scattering, this part (Part II) reports the progress that has been made in radiative transfer theories, models, and their common applications, focusing particularly on the contributions from Chinese researchers. The recent achievements on radiative transfer models and methods developed for weather and climate studies and for atmospheric remote sensing are firstly reviewed. Then, the associated applications, such as surface radiation estimation, satellite remote sensing algorithms, radiative parameterization for climate models, and radiative-forcing related climate change studies are summarized, which further reveals the importance of radiative transfer theories and models.